A talent for murder : a novel - Swanson, Peter, 1968- (Henry Kimball/Lily Kintner, 2024)
"Martha Ratliff conceded long ago that she'd likely spend her life alone. She was fine with it, happy with her solo existence, stimulated by her work as a librarian in Maine. But then she met Alan, a charming and sweet-natured salesman whose job took him on the road for half the year. When he asked her to marry him, she said yes, even though he still felt a little bit like a stranger. A year in and the marriage was good, except for that strange blood streak on the back of one of his shirts he'd worn to a conference in Denver. Her curiosity turning to suspicion, Martha investigates the cities Alan visited over the past year and uncovers a disturbing pattern--five unsolved cases of murdered women. Is she married to a serial killer? Or could it merely be a coincidence? Unsure what to think, Martha contacts an old friend from graduate school for advice. Lily Kintner once helped Martha out of a jam with an abusive boyfriend and may have some insight. Intrigued, Lily offers to meet Alan to find out what kind of man he really is . . .but what Lily uncovers is more perplexing and wicked than they ever could have expected"--